Análise de fragilidade ambiental como subsídio para a gestão da Bacia do rio Alambari, região de Botucatu (SP) - Volpi, Tomás Carvalhaes (Universidade Federal de São Carlos, 2025)
The Alambari River Basin is located in the municipalities of Botucatu, Anhembi, and Bofete, in the state of São Paulo, Brazil. Originating in the Western Paulista Plateau, its drainage crosses the Botucatu Cuesta, extends through the Peripheral Depression, and flows into the Tietê River at the Barra Bonita reservoir. The geomorphology of this region has been the subject of classic studies in Brazilian geography and contributes unique features to the landscape and environmental dynamics. This study is based on a systemic theoretical framework and uses the empirical methodology of environmental fragility, supported by Geographic Information Systems (GIS). The predominant land cover and use types are pastures, forest formations, and silviculture. High environmental fragility prevails, with soil erosion identified as the main environmental issue. There is a clear need for enforcement and restoration of preservation areas, improvements in agricultural management, and incentives for agroecological systems.
Environmental Fragility Analysis as a Basis for the Management of the Alambari River Basin, Botucatu Region (São Paulo, Brazil)
Keywords: Cuestas Paulistas; Paisagem; Fragilidade Ambiental; Planejamento Ambiental; Landscape; Environmental Fragility; Environmental Planning; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA; CIENCIAS HUMANAS::GEOGRAFIA